Sprachatlas des Dolomitenladinischen und angrenzender Gebiete Band 4 - Goebl, Hans (Editions de Linguistique et de Philologie, 2012)
The fourth volume contains 215 dialect maps which embrace dialectal terminologies from the seasons to the domestic animals.